IMPACT OF AN ANTIBIOTIC STEWARDSHIP INTERVENTION ON ANTIBIOTIC USE AND HEALTH-CARE-ASSOCIATED INFECTION RATES (Journal of Medical & Health Sciences Review, 2025)
Background: Antimicrobial resistance is a global health threat, driven in large part by irrational antibiotic prescribing in hospitals. Antibiotic stewardship programs (ASPs) are evidence-based strategies to optimize antibiotic use, reduce resistance, and improve patient outcomes. This study evaluated the impact of an antibiotic stewardship intervention on antibiotic consumption and health-care-associated infection (HAI) rates at Ch. Pervaiz Elahi Institute of Cardiology, Multan.Methods: A prospective interventional study was conducted on 300 patients admitted between January and June 2025. Patients were divided into two groups: pre-intervention (n=150) and post-intervention (n=150). The stewardship program included prescriber education, guideline dissemination, and audit-feedback mechanisms. Outcomes assessed included antibiotic consumption, appropriateness of prescribing, and incidence of HAIs. Data were analyzed using chi-square and t-tests, with p